Chiefs: Sense of Belonging versus Power and Politics - Pauwels, Simonne (Anthropologica, 2020)
As a guideline to reading the articles of the thematic section “Chiefs of the Pacific,” this introduction suggests differentiating sacred chiefs and secular chiefs, understanding them respectively as a person receiving respect and supplying blessings in a hierarchical order and as the same person (or another) when the context changes to attribute political and/or economic power to them and put them at the summit of a social stratification. The four articles illustrate how this distinction became particularly useful after colonization.